Isolation of pseudocapacitive surface processes at monolayer MXene flakes reveals delocalized charging mechanism - Marc Brunet Cabré; Dahnan Spurling; Pietro Martinuz; Mariangela Longhi; Christian Schröder; Hugo Nolan; Valeria Nicolosi; Paula E. Colavita; Kim McKelvey (Nature Communications, 2023)
MXenes are two-dimensional nanomaterials that can be used as supercapacitors to store electrical energy. Here, the authors isolated chemical response from a single MXene flake and provide a new understanding of the surface chemistry of MXenes.